The Impact of Poverty, Education Spending, and Village Funds on the Human Capital Index in the Nias Islands - Berutu, Saiful Ragatna; Lubis, Irsad (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The Human Development Index can be used as an indicator of successful development in a country or region. In 2023, the lowest Human Development Index in North Sumatra Province was in the Nias Islands, namely West Nias Regency (63.70), South Nias Regency (64.13), Nias Regency (64.56), and North Nias Regency (64.64). Only Gunungsitoli City ranks in the lowest 10 out of 33 regencies/cities with an index of 70.68. This study aims to determine whether Poverty, Education Expenditure, and Village Funds have an impact on the Human Development Index in the Nias Islands. The results showed that partially Poverty has a negative and significant impact, Education Expenditure has a positive but insignificant impact, and Village Funds have a positive and significant impact on the Human Development Index in the Nias Islands. Poverty, education expenditure, and village funds simultaneously have a significant impact on the Human Development Index. Poverty, education expenditure, and village funds can explain the Human Development Index by 93.766%. The remaining 6.234% is accompanied by other variables that are not included in the object of this study. Therefore, the Government should create programs for poverty alleviation and optimize Education Expenditure and Village Funds to increase the Human Development Index in the Nias Islands.